2019
DOI: 10.1371/journal.pone.0218620
|View full text |Cite
|
Sign up to set email alerts
|

Assessing urban-rural differences in the relationship between social capital and depression among Ghanaian and South African older adults

Abstract: Introduction Research has demonstrated benefits of social capital on depression, but variations in this relationship by geographic characteristics such as urbanicity have rarely been investigated. Methods Using survey data on 4,209 Ghanaian and 3,148 South African adults aged 50 and above from the World Health Organization (WHO) Study on Global AGEing and Adult Health (SAGE), exploratory and confirmatory factor analyses were conducted to extract dimensions of social cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
3
6
1
Order By: Relevance
“…Despite the scarcity of social capital intervention studies, there are some which show social capital interventions that promote community engagement and social participation are associated with better physical health [ 43 45 ]. In addition, though prior research on depression suggested differences may exist in the relationship with social capital by area of residence [ 46 , 47 ], this study found that there was no differential relationship between hypertension and social capital by rural/urban status. Detailed investigation into how social capital is built and how that influences health in a variety of situations will be necessary to understand this complex relationship.…”
Section: Discussioncontrasting
confidence: 75%
“…Despite the scarcity of social capital intervention studies, there are some which show social capital interventions that promote community engagement and social participation are associated with better physical health [ 43 45 ]. In addition, though prior research on depression suggested differences may exist in the relationship with social capital by area of residence [ 46 , 47 ], this study found that there was no differential relationship between hypertension and social capital by rural/urban status. Detailed investigation into how social capital is built and how that influences health in a variety of situations will be necessary to understand this complex relationship.…”
Section: Discussioncontrasting
confidence: 75%
“…A considerable amount of literature suggests a difference in risk of many chronic diseases, disability, mental condition, and social engagement among older populations by their place of residence (urban and rural) 23 , 24 . It is mainly because of economic inequality, unequal accessibility to various type of health care services, and involvement gap in diverse social activities between urban and rural dweller elderly 25 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The differences in the association between rurality and depression and the mechanisms underlying the variation across geographical units have received little attention among studies of the urban–rural depression gap. A study performed in Ghana and South Africa found no substantial urban–rural differences in the strength of the association between social capital and depression [ 48 ]. In a report from China that focused on the impact of rapid urbanization on social capital and health, the association between social capital and depression varied by period and rurality [ 49 ].…”
Section: Discussionmentioning
confidence: 99%